The spider cuticle: a remarkable material toolbox for functional diversity. (20th September 2021) - Politi, Yael; Bertinetti, Luca; Fratzl, Peter; Barth, Friedrich G.
Abstract : Engineered systems are typically based on a large variety of materials differing in composition and processing to provide the desired functionality. Nature, however, has evolved materials that are used for a wide range of functional challenges with minimal compositional changes. The exoskeletal cuticle of spiders, as well as of other arthropods such as insects and crustaceans, is based on a combination of chitin, protein, water and small amounts of organic cross-linkers or minerals. Spiders use it to obtain mechanical support structures and lever systems for locomotion, protection from adverse environmental influences, tools for piercing, cutting and interlocking, auxiliary structures for the transmission and filtering of sensory information, structural colours, transparent lenses for light manipulation and more. This paper illustrates the 'design space' of a single type of composite with varying internal architecture and its remarkable capability to serve a diversity of functions. This article is part of the theme issue 'Bio-derived and bioinspired sustainable advanced materials for emerging technologies (part 1)'.